Mitochondrial protein BNIP3 regulates Chikungunya virus replication in the early stages of infection. - Liliana Echavarria-Consuegra; Nilima Dinesh Kumar; Marleen van der Laan; Mario Mauthe; Denise Van de Pol; Fulvio Reggiori; Jolanda M Smit (Public Library of Science (PLoS), 2023)
Chikungunya virus (CHIKV) is a human pathogen causing outbreaks of febrile illness for which vaccines and specific treatments remain unavailable. Autophagy-related (ATG) proteins and autophagy receptors are a set of host factors that participate in autophagy, but have also shown to function in other unrelated cellular pathways. Although autophagy is reported to both inhibit and enhance CHIKV replication, the specific role of individual ATG proteins remains largely unknown. Here, a siRNA screen was performed to evaluate the importance of the ATG proteome and autophagy receptors in controlling CHIKV infection. We observed that 7 out of 50 ATG proteins impact the replication of CHIKV. Among those, depletion of the mitochondrial protein and autophagy receptor BCL2 Interacting Protein 3 (BNIP3) increased CHIKV infection. Interestingly, BNIP3 controls CHIKV independently of autophagy and cell death. Detailed analysis of the CHIKV viral cycle revealed that BNIP3 interferes with the early stages of infection. Moreover, the antiviral role of BNIP3 was found conserved across two distinct CHIKV genotypes and the closely related Semliki Forest virus. Altogether, this study describes a novel and previously unknown function of the mitochondrial protein BNIP3 in the control of the early stages of the alphavirus viral cycle.